Inventory Management System Framework Based on Python and MySQL Database with Blockchain Technology Implementation - Zainur Romadhon (Lembaga Pengembangan Kinerja Dosen, 2025)
Efficient and transparent inventory control is increasingly crucial for sustaining supply chain performance in the digital age. Conventional systems often face challenges such as poor visibility, vulnerability to data manipulation, and inefficiencies in stock monitoring. To address these issues, this research proposes a novel inventory management framework integrating Python, MySQL, and blockchain technology, following a Research and Development (R&D) methodology involving need assessment, system design, implementation, testing, and validation. The framework utilizes Python as the core programming language, MySQL for structured data management, and blockchain as a decentralized security layer to ensure data integrity and traceability. The system architecture consists of six main modules: inbound stock management, outbound stock management, blockchain-based storage, validation mechanisms, a user-friendly interface, and reporting tools. Black-box testing confirmed that all modules met their specifications, while security evaluations showed that the blockchain layer, with the SHA-256 hashing algorithm, effectively detected simulated data manipulation attempts. Performance testing revealed a linear increase in processing time relative to transaction volume, with the framework maintaining stability under medium-scale operational loads. This study contributes to the literature on blockchain-enabled inventory systems by introducing a structured, integrative model, and provides a practical framework that enhances efficiency, transparency, and accountability in inventory management. Future research is encouraged to explore scalability challenges and optimize consensus mechanisms for large-scale applications.